The development of legal aid in criminal case of Thailand - Pasit Asawawattanaporn (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Legal aid, in the scope of the assistance from the authority to appoint a lawyer for (an accused or) a defendant in criminal cases, has been in Thailand's legal system since the promulgation of the Criminal Procedure Code. However, its existence in the Code does not fulfil the goal of the concept of the Rule of Law. Although Thailand has amended the Code for a number of times, the assistance does not help the intended people in a practical way. This researched touch upon the problems of Thailand's legal system (on this issue) and attempted to find a way to develop improve its efficiency and effectiveness. The research adopted a qualitative methodology, comprised at documentary research, exploring the system in various countries. and an in depth interview with experts. The targets population of this study were a total of 10 people involved in providing legal aid. It was found in this study that the lack of effective legal aid in Thailand could be classified into 3 types (1) Eligibility problems (2) Appointment process and quality of lawyer problems and (3) Administration problems. The key factors in all the problems were, the lack of proper legislation to direct the roles and responsibility of involving authorities, as well as the lack of proper agency in charge of the scheme. This research proposed that the state should enact a specific legislation purposefully dealing with the scheme. This new legislation could be an amendment to the Act of Justice Fund 2015 to elevate the Fund to be an exclusive agency in charge of the scheme. Eligibility should be explicitly provided in the amendment. The Fund should have a system to control the quality of lawyers listed the Fund. Finally, in order to ensure quality service the internal audit and the external audit should be set up. Future research should explore the Courts' power to ensure good service of appointedlawyers. and the right of defendants to choose lawyers .